Bronchiolitis at a specialist paediatric centre: The electronic medical record helps to evaluate low‐value care. (25th August 2019) - Lawrence, Joanna G; Andrew, Lauren; Bracken, Jenny; Voskoboynik, Alice; Oakley, Ed; South, Mike; Middleton, Katherine; Scanlan, Barry; Marshall, Tim; Hiscock, Harriet
Abstract : Aim: Low‐value care (LVC) is common. We aimed, using infants presenting to a major tertiary paediatric hospital with bronchiolitis between April 2016 and July 2018, to: (i) assess rates of chest X‐ray (CXR) and medication use; (ii) identify associated factors; and (iii) measure the harm of not performing these practices. Methods: We extracted data from the electronic medical record for all children aged 1–12 months given a diagnosis of bronchiolitis in the emergency department. Factors potentially associated with LVC practices were extracted, including patient demographics, ordering physician characteristics, order indication, medications prescribed and admission ward. To assess for harm, a radiologist, blinded to CXR indication, reviewed all CXRs ordered over the winter of 2017 for infants with bronchiolitis. Results: A CXR was ordered for 439 (11.2%) infants, most commonly to rule out consolidation and collapse (65%). CXRs were more likely to be ordered for admitted infants (40.9% admitted to the general medical ward), and 62% were ordered by emergency department staff. Salbutamol was prescribed for 9.3% ( n = 199). Amongst those who had a CXR, 28% were prescribed an antibiotic compared to 2.1% for those who did not. In an audit of 98 CXRs ordered over the winter of 2017, there were no CXR findings that meaningfully affected patient outcomes. Conclusion: Using electronic medical record data, we found that CXR and medication use in bronchiolitis were higher than expected given our hospital guideline advice. Future research needs to understand why and develop interventions to reduce LVC.